RETRACTED: Spermatogonial stem-cell-derived neural-like cell transplantation enhances the functional recovery of a rat spinal cord injury model: characterization of evoked potentials - Guo, Xinyu; Jiang, Chao; Zhang, Yongjie; Chen, Zhe; Hao, Dingjun; Zhang, Haihong (Frontiers in Neuroscience, 2023)
Severe spinal cord injuries (SCIs) usually result in the temporary or permanent impairment of strength, sensation or autonomic functions below the sites of injuries. To date, a large number of therapeutic approaches have been used to ameliorate SCIs, and subsequent stem cell transplantation appears to be a promising strategy. The aim of this study was to evaluate the therapeutic effect of stem cells by changes in the evoked potentials at different time points after a transplantation of spermatogonial stem cells (SSCs) to differentiate the source neurons in a rat model with SCIs, as well as through histopathology. A modified Plemel spinal cord lateral compression model was used. The experiment was divided into a blank, a control and a SSC transplantation group. Motor activity scores, sensory evoked potentials (SEPs) and motor evoked potentials (MEPs) were assessed through motor resuscitation as well as histologic evaluation on each experimental group to determine the improvement. Consistent with our results, motor scores and evoked potentials were significantly improved in the SSC transplantation group. In addition, a histologic assessment showed that the transplanted stem cells had a significant restorative effect on the reconstruction of tissue cells. 1 week after the stem cell transplantation, the SSC transplantation group showed improvement in spinal cord functions and spinal cord pathologic injuries. After 2 weeks and beyond, the SSC transplantation group showed significant improvement in spinal cord functions and spinal cord pathology compared to the control group, meanwhile the evoked potentials and motor function of the hind limbs of rats in the SSC transplantation group were significantly improved. Therefore, the therapeutic strategies for spermatogonial stem cells will be an effective program in the study on SCIs, and we suggest the somatosensory evoked potentials as a tool to assess the degree of recovery from SCIs after the transplantation of stem cells.